Faktor-faktor Yang Mempengaruhi Opini Audit Going Concern - Edy Suprianto; Ramadhani Rizal Rinardi (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2022)
Abstract The purpose of this study was to analyze the factors that influence going concern audit opinion. The population in this study were all companies listed on the Indonesia Stock Exchange. The sample was selected by purposive sampling method, in order to obtain 1002 observations (company/year). Data were analyzed using logistic regression analysis model. Based on the results of the analysis, it can be concluded that only the variables of previous year's audit opinion and opinion shopping have an effect on going concern audit opinion. While the variables of financial statement disclosure, debt default, and company size have no effect on going concern audit opinion. This indicates that it is important for the company to pay attention to the previous audit opinion to be able to obtain a going concern opinion from the auditor. Keywords: disclosure of financial statements, debt default, size of the company, audit opinion in the previous year, opinion shopping, going concern audit opinion Abstrak Tujuan penelitian ini adalah untuk menganalisis faktor-faktor yang mempengaruhi opini audit going concern. Populasi dalam penelitian ini adalah seluruh perusahaan yang terdaftar di Bursa Efek Indonesia. Sampel dipilih dengan metode purposive sampling, sehingga diperoleh 1002 observasi (perusahaan/tahun). Data dianalisis dengan menggunakan model analisis regresi logistic. Berdasarkan hasil analisis dapat disimpulkan bahwa hanya variable Opini audit tahun sebelumnya dan Opinion Shopping yang berpengaruh terhadap opini audit going concern. Sedangkan variable disclosure laporan keuangan, debt default, dan ukuran perusahaan tidak berpengaruh terhadap opini audit going concern. Hal ini mengindikasikan bahwa penting bagi perusahaan untuk memperhatikan opini audit sebelumnya untuk dapat memperoleh opini going concern dari auditor. Kata kunci: disclosure laporan keuangan, debt default, ukuran perusahaan, opini audit tahun sebelumnya, opinion shopping, opini audit going concern.